1986
DOI: 10.1177/000456328602300108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Aldosterone Radioimmunoassay: The Renin—Angiotensin—Aldosterone Axis as a Function of Sex and Age

Abstract: SUMMARY.A highly specific radioimmunoassay for aldosterone in plasma has been developed utilising extraction from plasma into dichloromethane, an antiserum raised to aldosterone-3-carboxy-methyloxime-BSA and a radio-iodinated derivative of aldosterone. The plasma values obtained after only extraction correlated very well with the results following chromatography over celite. The within-and between-batch variations for plasma pools ranged between 5 and 15%. The range obtained, HXl-1806 pmoVL for 96 random uprig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…However, numerous studies have shown an overlap between aldosterone levels in 24-h urine collections in patients with primary aldosteronism and with essential hypertension [22][23][24], although the urinary determination of tetrahydroaldosterone seems to be more promising, as recently proposed [25]. APA, Aldosterone-producing adenoma; IHA: idiopathic hyperaldosteronism; PRA, plasma renin activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies have shown an overlap between aldosterone levels in 24-h urine collections in patients with primary aldosteronism and with essential hypertension [22][23][24], although the urinary determination of tetrahydroaldosterone seems to be more promising, as recently proposed [25]. APA, Aldosterone-producing adenoma; IHA: idiopathic hyperaldosteronism; PRA, plasma renin activity.…”
Section: Discussionmentioning
confidence: 99%
“…We have considerably expanded this concept. To establish the usefullness of the PA/PRA ratio in the screening for aldosterone disorders, it was necessary to expand our experience with normal subjects, which had previously been confined to upright values (8), to a variety of stable and unstable conditions. Although PA and PRA varied significantly with lying and standing and with variations in salt intake, the PA/PRA ratio was constant.…”
Section: Discussionmentioning
confidence: 99%
“…Additional samples were obtained from some in-patient subjects after overnight recumbency. PA was measured using a highly specific RIA, previously described from this laboratory (8). PRA was measured using a CEA Sorin (Vercielli, Italy) kit to estimate the generation of angiotensin-I by RIA (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum creatinine was normal and plasma renin activity (PRA) and aldosterone levels after 2 h of upright posture were measured at 31.9 ng/ml/h (upper limit of normal in young women: 10.5 ng/ml/h [5]) and 19.9 ng/dl (upper limit of normal in young women: 43.6 ng/dl [5]), respectively, while taking captopril 12.5 mg twice daily. Intravenous pyelography, renal angiography and renal CT were normal.…”
Section: Casementioning
confidence: 99%